Perturbation of EPHA2 and EFNA1 trans binding amplifies inflammatory response in airway epithelial cells - Ryosuke Fukuda; Shiori Beppu; Daichi Hinata; Yuka Kamada; Tsukasa Okiyoneda (iScience)
Summary: The interactions between EPH receptors and ephrin (EFN) ligands play a crucial role in maintaining epithelial integrity and aiding in defense against infections. However, it remains unclear how the EPH-EFN trans-binding changes during infections and how this alteration affects inflammatory response. Here we report that pathogen-associated molecular patterns (PAMPs) disrupt the EPHA2-EFNA1 trans-binding in airway epithelial cells (AECs). Mechanistically, flagellin induces the TLR5-dependent EFNA1 cleavage through the metalloproteinase ADAM9 concomitant with the activation of ligand-independent EPHA2 signaling. We found that the ablation of EPHA2 reduced the responsiveness of respiratory inflammation induced by flagellin and Pseudomonas aeruginosa both in vitro and in vivo. Notably, even in the absence of PAMPs, the inflammatory response in AECs was stimulated by forcibly induced EFNA1 shedding. These findings illustrate that the perturbation of the EPHA2-EFNA1 trans-binding acts as a sensing mechanism for infections and amplifies the inflammatory response, providing a defense mechanism for respiratory epithelia.